Development of Nanoparticles Pegagan Leaves Ethanolic Extract (centella asiatica (L.) Urban) using Variation Concentration of Poly-Lactic-CO-Glycolic Acid (PLGA) Polymer - Elsa Fitria Apriani; Mardiyanto Mardiyanto; Rika Destiana (Majalah Obat Tradisional, 2022)
Pegagan is a plant that plays an important role in health because of its secondary metabolite. However, many secondary metabolites tend to be unstable when exposed to UV light and oxygen such as flavonoid and terpenoid. The purpose of this study was to formulate the ethanolic extract of pegagan leaves into nanoparticle preparations to increase the stability of the extract. Nanoparticle preparations were made using the emulsion solvent evaporation method using Poly-Lactic-Co-Glycolic Acid (PLGA) and polyvinyl alcohol (PVA). PLGA acts as a polymer that will coat the extract and PVA as a stabilizer. Variations in the concentration of PLGA used were 50 mg, 75 mg, and 100 mg, while the concentration of PVA used was 40 mg and the extract concentration was 158 mg. Determination of the best formula is done by looking at the results of the percent encapsulation efficiency obtained from the three formulas, namely 93.68%, 85.35%, and 88.76%, respectively. Based on these results, formula 1 was determined as the best formula. The particle size obtained in the best formula was 288.1667±3.4195 nm, the polydispersity index (PDI) was 0.371±0.0045 and the zeta potential value was -10.6333±0.1154. A physical stability test (cycling test method) of the best formula found a decrease in pH of 0.54 and no organoleptic changes or precipitate formed.